Left Atrial Hypertension, Electrical Conduction Slowing, and Mechanical Dysfunction – The Pathophysiological Triad in Atrial Fibrillation-Associated Atrial Cardiomyopathy - Eichenlaub, Martin; Mueller-Edenborn, Bjoern; Minners, Jan; Jander, Nikolaus; Allgeier, Martin; Lehrmann, Heiko; Schoechlin, Simon; Allgeier, Juergen; Trenk, Dietmar; Neumann, Franz-Josef; Arentz, Thomas; Jadidi, Amir (Frontiers in Physiology, 2021)
Background Atrial fibrillation (AF) is the most common arrhythmia and a significant burden for healthcare systems worldwide. Presence of relevant atrial cardiomyopathy (ACM) is related to persistent AF and increased arrhythmia recurrence rates after pulmonary vein isolation (PVI). Objective To investigate the association of left atrial pressure (LAP), left atrial electrical [invasive atrial activation time (IAAT) and amplified p-wave duration (aPWD)] and mechanical [left atrial emptying fraction (LA-EF) and left atrial strain (LAS)] functional parameters with the extent of ACM and their impact on arrhythmia recurrence following PVI. Materials and Methods Fifty patients [age 67 (IQR: 61–75) years, 78% male] undergoing their first PVI for persistent AF were prospectively included. LAP (maximum amplitude of the v-wave), digital 12-lead electrocardiogram, echocardiography and high-density endocardial contact mapping were acquired in sinus rhythm prior to PVI. Arrhythmia recurrence was assessed using 72-hour Holter electrocardiogram at 6 and 12 months post PVI. Results Relevant ACM (defined as left atrial low-voltage extent ≥2 cm2 at <0.5 mV threshold) was diagnosed in 25/50 (50%) patients. Compared to patients without ACM, patients with ACM had higher LAP [17.6 (10.6–19.5) mmHg with ACM versus 11.3 (7.9–14.0) mmHg without ACM (p = 0.009)]. The corresponding values for the electrical parameters were 166 (149–181) ms versus 139 (131–143) ms for IAAT (p < 0.0001), 163 (154–176) ms versus 148 (136–152) ms for aPWD on surface-ECG (p < 0.0001) and for the mechanical parameters 27.0 (17.5–37.0) % versus 41.0 (35.0–45.0) % for LA-EF in standard 2D-echocardiography (p < 0.0001) and 15.2 (11.0–21.2) % versus 29.4 (24.9–36.6) % for LAS during reservoir phase (p < 0.0001). Furthermore, all parameters showed a linear correlation with ACM extent (p < 0.05 for all). Receiver-operator-curve-analysis demonstrated a LAP ≥12.4 mmHg [area under the curve (AUC): 0.717, sensitivity: 72%, and specificity: 60%], a prolonged IAAT ≥143 ms (AUC: 0.899, sensitivity: 84%, and specificity: 80%), a prolonged aPWD ≥153 ms (AUC: 0.860, sensitivity: 80%, and specificity: 79%), an impaired LA-EF ≤33% (AUC: 0.869, sensitivity: 84%, and specificity: 72%), and an impaired LAS during reservoir phase ≤23% (AUC: 0.884, sensitivity: 84%, and specificity: 84%) as predictors for relevant ACM. Arrhythmia recurrence within 12 months post PVI was significantly increased in patients with relevant ACM ≥2 cm2, electrical dysfunction with prolonged IAAT ≥143 ms and mechanical dysfunction with impaired LA-EF ≤33% (66 versus 20, 50 versus 23 and 55 versus 25%, all p < 0.05). Conclusion Left atrial hypertension, electrical conduction slowing and mechanical dysfunction are associated with ACM. These findings improve the understanding of ACM pathophysiology and may be suitable for risk stratification for new-onset AF, arrhythmia recurrence following PVI, and development of novel therapeutic strategies to prevent AF and its associated complications.